Implementing Labor Standards in the Electronics Sector of Hungary: Interactions Across Public and Private Governance Approaches - Pal, Timea (Labor Standards in Electronics Sector of Hungary, 2015)
This article proposes a theoretical framework to analyze interactions across private and public regulatory governance in transnational production chains, and uses the electronics industry of Hungary to evaluate its empirical relevance. The key argument is that implementation of labor standards is contingent on combining private and public approaches with complementary competences with respect to the legitimacy, commitment and capacity of regulatory governance. Improvements in the working conditions of subcontracted employees at two major electronics facilities in Hungary, for example, were greatly facilitated by the coexistence of national legislation, on one hand, and the significant enforcement capacity of their lead corporations, eager to limit criticism by labor and civil society organizations, on the other. Similar conditions, however, were largely absent around the issues of working time and disciplinary measures, resulting only in modest to no improvements, respectively. The second main argument is that the complementary features do not translate into improvements in an automatic manner, but need to be activated through the strategic actions of regulatory agents. Implementation of labor standards at the facility integrated into the monitoring-oriented private governance approach were driven were driven mainly through the legitimizing efforts of the private auditors. At the facility governed by a stakeholder-oriented approach, on other hand, processes of change were set in place by the labor union empowered by the lead private governance institution.